Impact of Social Media on Mental Health and Well-Being across Different Cultures and Age Groups in Nepal - Chaha, Bilhana (International Journal of Psychology, 2024)
Purpose: The aim of the study was to investigate impact of social media on mental health and well-being across different cultures and age groups Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Social media's impact on mental health and well-being varies across cultures and age groups. While it can foster social connection, information sharing, and creativity, it also contributes to negative outcomes such as social comparison, cyberbullying, and sleep disruption. Cultural norms influence how individuals engage with social media, and age-related factors shape susceptibility to its effects, highlighting the need for nuanced approaches to promoting digital well-being. Unique Contribution to Theory, Practice and Policy: Social comparison theory, cultural learning theory & uses and gratifications theory may be used to anchor future studies on impact of social media on mental health and well-being across different cultures and age groups. Develop culturally sensitive interventions and digital literacy programs that equip individuals with the skills to navigate social media platforms in ways that promote mental well-being. Advocate for evidence-based policies that protect vulnerable populations from the harmful effects of social media while promoting digital inclusion and empowerment.